PENGENALAN OBAT ANTIBIOTIKA PADA PENGURUS CABANG AISYAH BLIGO KABUPATEN PEKALONGAN - Slamet Slamet; Wulan Agustin Ningrum; Eko Mugiyanto (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
Antibiotics are drugs used by doctors for the treatment of infections caused by microbes such as bacteria. Problems arise in the use of antibiotics that are not correct. Inappropriate use of antibiotics. The use of antibiotics that do not kill bacteria so that bacteria are resistant and antibiotic treatment does not work. The purpose of this community service is to remind you of the correct use of drugs and the consequences if antibiotic treatment is not correct. The method used is a lecture about antibiotics and infectious diseases that often occur in the community. The result of this service is that knowledge about antibiotic drugs and how to use them by Aisyah's caretakers is getting better which is reinforced by a high posttest score compared to the pretest value. The conclusion of the community service to the management of Aisyah's mothers is that their knowledge of antibiotics is getting better and those who have forgotten are reminded of their knowledge of antibiotics and their use.